Banks and Securities Markets: Corporate Financing in Germany and the United Kingdom. - Mayer, C; Alexander, I (1990)
This paper compares corporate financing in the German bank-based and U.K. market-based systems. Large German firms pay out a lower proportion of their profits as dividends and finance a larger proportion of their investments from retentions. German banks extend more long-term finance to medium-sized firms but U.K. firms raise more new equity. The paper tests alternative theories of corporate finance. It finds no relation between finance and taxation, andinformation theories only receive limited support. Instead, it concludes that control models of corporate finance are consistent with observed patterns of finance.